Tradisi Nyumpet dalam Budaya Lokal Pada Masyarakat Sekuro Kabupaten Jepara - Imanullah Hesti Nur Amala; Abdul Gafur (Universitas Andalas, 2020)
Culture is a custom made from long ago. The fundamental thing of culture is the presence of predecessors or ancestral information either written or unwritten. The local culture of java still in jepara district is a ‘nyumpet’ tradition. The study aims to describe how to preserve local culture in Indonesian tradition especially the ‘nyumpet’ tradition in jepara district securitate so society so that the younger generation will not forget the culture that has been built up long ago. This article was prepared using a library study method where the data obtained came from various books, journals, theses and several libraries from related sources. The scope of this study is expected to shape the fine young generation, responsible, and active generation of young people in local cultures. The ‘nyumpet’ tradition is a ritual performed by some people jepara kejawen. The nyumpet ritual is performed when there is a wedding ceremony or circumcision.